Understanding Cash Waqf Intention among Academics: The Role of Financial Literacy as a Moderating Variable - Zulkarnaen Zulkarnaen; Asyari Asyari; Hesi Eka Puteri; Aidil Alfin (Islamiconomic : Jurnal Ekonomi Islam, 2026)
Despite Indonesia’s substantial potential for cash waqf, its realization remains far below expectations, suggesting relatively low public interest in participating in such initiatives. This study aims to examine the effects of attitudes, subjective norms, religiosity, and information media on the intention to participate in cash waqf, with cash waqf literacy positioned as a moderating variable among lecturers of the Faculties of Islamic Economics and Business at State Islamic Religious Universities (PTKIN) in West Sumatra. This research employs a quantitative, survey-based approach. Primary data were collected via questionnaires distributed to 150 lecturers and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that attitudes, subjective norms, religiosity, and information media significantly and positively influence cash waqf intention. However, cash waqf literacy does not significantly moderate the relationships between these variables and cash waqf intention. These findings contrast with prior studies suggesting that cash waqf literacy plays a significant role in enhancing participation intention. The absence of a moderating effect indicates that the determinants proposed by the Theory of Reasoned Action (TRA) exert a strong, direct influence independent of literacy levels. In practice, the results imply that waqf institutions and nazhir should reconsider their strategic focus, shifting from literacy-based campaigns to strengthening transparency, trust, and institutional credibility, particularly when targeting academics and upper-middle-class Muslim communities.